ANALISIS EFEKTIVITAS PENERAPAN PROSES REKRUTMEN ONLINE PADA SALAH SATU PT PENYEDIA TENAGA KERJA DIKOTA GRESIK - Ramadhani, Farosah; Amalina Rizqi, Maulidyah (Jurnal Bisnis dan Kewirausahaan, 2024)
This research discusses the effectiveness of the implementation of the online recruitment process at PT Penyedia Tenaga Kerja dikota Gresik. The company uses a descriptive qualitative method that refers to online recruitment data since 2016, involving digital platforms, websites, and specialized applications. The recruitment process involves the stages of file selection, interview tests, written and technical tests, and orientation and evaluation. Interviews with informants from the company show that PT Penyedia Tenaga Kerja dikota Gresik measures the success of online recruitment based on criteria such as the number of quality candidates, complete resumes, appropriate domicile, appropriate age, and potential to become an expert in the field. The company's strategy to improve the quality of prospective employees involves detailing advertisements, extracting information and talents of prospective employees, and improving document selection filters. The company evaluates the effectiveness of its online recruitment platform by looking at the number of qualified applicants, the success of meeting employee needs, and the platform's ability to save time and money. In managing relationships with candidates, the company focuses on friendly communication and ensuring candidates feel comfortable. Based on data analysis, PT Penyedia Tenaga Kerja dikota Gresik has implemented online recruitment effectively. However, challenges such as mismatches between educational backgrounds and desired jobs need to be addressed. Continuous evaluation of the online recruitment process as well as adjustments to technological developments and labor market dynamics are recommended to ensure the company's continued success in obtaining quality employees.